ANALISIS HARGA DAN KERAGAMAN PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEAGAI VARIABEL INTERVENING PADA TOKO AMANAH DI SITUBONDO - Cahyani, Andita Zahariya; Ediyanto, Ediyanto; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2023)
Marketing has a significant influence on consumer purchases of the products or services offered, for marketing success, both in terms of product and service marketing. The purpose of this research is to analyze and test the effect of price and product variety in determining consumer satisfaction with purchase decision as a variable. intervene. The population in this study are consumers of trust shops in Situbondo. The sampling method was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that price has a significant positive effect on purchasing decisions, product variety has a significant effect on purchasing decisions, price has no significant effect on consumer satisfaction, product variety has no significant effect on customer satisfaction, purchasing decisions have a significant effect positive on consumer satisfaction. The results of the indirect effect hypothesis show that the price variable on consumer satisfaction through purchasing decisions has a significant positive effect, product variety on consumer satisfaction through purchasing decisions does not have a significant effect.